Comparison of Epinephrine and Salbutamol Nebulization in Acute Bronchiolitis in terms of mean change in RDAI Score - Anam Zafar, Nahdia Zaman, Muhammad Salman Shafique, Shahzadi Sumbal Ghazi, Maryam Amjad, Sughra Wahid (Journal of Rawalpindi Medical College, 2021)
Objective: This study was conducted to compare epinephrine and salbutamol nebulization in emergency management of moderately ill children less than one and a half years old with bronchiolitis in terms of mean change in respiratory distress assessment instrument (RDAI) score. Materials and Methods: Randomized controlled design was selected in this trial at the Department of Pediatrics, KRL Hospital Islamabad, Pakistan from 24th April 2016 to 24th October 2016. Sixty children with acute bronchiolitis, having a moderate degree of illness (RDAI 8-15) were included in this study. Patient were randomly allocated into Group A (epinephrine = 0.1 mL/kg in concentration of 1:10000) and Group B (salbutamol = 0.15 mg/kg combined with 3 mL 0.9% normal saline). It was delivered by a nebulizer and a face mask with a continuous flow of 6 L/min at100% oxygen. Data was collected on a predesigned performa and assessed with reference to mean change in RDAI score. Results: The patients ' mean age in Group A and Group B were 10.57±4.22 and 11.63±3.14 months, respectively. The majority of the patients were males (56%). The mean RDAI score was insignificant between the two groups, both at baseline (11.57±2.21 in epinephrine group vs 11.3±2.14 in salbutamol group, p = 0.63) and 125 minutes (4.77±2.19 in Epinephrine group vs 5.43±1.69 in Salbutamol group, p = 0.19). However, when stratified according to age and gender, the mean RDAI score was found statistically significant among the 2-12 months age group (p = 0.0045) and female gender (p = 0.0052). Conclusion: Epinephrine and salbutamol have similar effects in acute bronchiolitis when compared with regards to mean change in RDAI score.